2012
DOI: 10.1002/jez.1738
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Restraint Stress on Lead‐Induced Male Reproductive Toxicity in Rats

Abstract: This study was undertaken to investigate whether chronic immobilization stress interferes with lead-induced reproductive toxicity in rats. Early pubertal male Wistar rats were subjected to either restraint stress (5 hr/day) or maintained on lead (0.15%) containing water or both for 60 days. Restraint stress or lead treatment significantly decreased the weight of the testes and epididymis. The daily sperm production, epididymal sperm count, sperm motility, and sperm viability were also decreased after exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 61 publications
4
26
0
Order By: Relevance
“…In fact, many of the conditions which are known to have detrimental effects to male reproductive system are due to an induction of oxidative stress [89]. Besides altering hormonal changes, EDCs are also known to induce oxidative stress through a reduction of antioxidant enzyme (e.g., superoxide dismutase, dismutase, catalase and glutathione peroxidase) activities and/or an increase in lipid peroxidation [33,90-92]. In addition, EDC-induced oxidative stress was found to disrupt cell adhesion protein function between testicular cells through the phosphorylation of phosphoinositide 3-kinase/c-Src/focal adhesion kinase (PI3K/c-Src/FAK) signaling cascade [88].…”
Section: Impact Of Edcs On Induction Of Reaction Oxygen Speciesmentioning
confidence: 99%
“…In fact, many of the conditions which are known to have detrimental effects to male reproductive system are due to an induction of oxidative stress [89]. Besides altering hormonal changes, EDCs are also known to induce oxidative stress through a reduction of antioxidant enzyme (e.g., superoxide dismutase, dismutase, catalase and glutathione peroxidase) activities and/or an increase in lipid peroxidation [33,90-92]. In addition, EDC-induced oxidative stress was found to disrupt cell adhesion protein function between testicular cells through the phosphorylation of phosphoinositide 3-kinase/c-Src/focal adhesion kinase (PI3K/c-Src/FAK) signaling cascade [88].…”
Section: Impact Of Edcs On Induction Of Reaction Oxygen Speciesmentioning
confidence: 99%
“…Restraint stress is widely utilized to mimic the psychological stress in many studies, in which the individual is isolated from its group and his movement is confined to a restricted area 16 , 17 . Increasing evidence demonstrates that chronic stress, including restraint stress, results in a significant decline in the quality of semen 18 20 , which could be related to a disruption in testosterone secretion in testes 20 22 , and an increase of oxidative stress 20 , 23 , 24 , and apoptosis of germ cells 19 , 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is one of the major factors that induce testicular cells apoptosis in testes 35 37 . Several studies showed that stress induced alterations in spermatogenesis potentially due to the increased oxidative stress in testes 20 , 23 , 24 . In addition, some other studies demonstrated that melatonin has an anti-apoptotic effect in somatic and germ cells 22 , 38 40 .…”
Section: Introductionmentioning
confidence: 99%
“…According to relevant reports, pachytene spermatocytes and early spermatids are the most sensitive testicular cells to thermal stress (Hari Priya & Reddy, ; Wallach, Kandeel, & Swerdloff, ). Additionally, it has been illustrated that HS can lead to testicular weight reduction, sperm dysfunction and sperm mortality increase (Ebeid, ; McDaniel, Hood, & Parker, ).…”
Section: Introductionmentioning
confidence: 99%